Development of Helium Isotope Reference Materials near Ambient 3He/4He Ratio. (11th September 2018) - Kim, Jeong Eun; Yang, Inseok; Kim, Jin Seog
Abstract : The 3 He/ 4 He ratio in the atmosphere is known to be 1.34 × 10 −6 . For accurate measurement of low 3 He concentrations, a certified reference material (CRM) with a low 3 He/ 4 He ratio is necessary. In this work, we produced a new 3 He CRM of helium isotopic ratio standard by the gravimetric method with a 3 He concentration similar to that of the atmospheric air. Previously, a helium isotope CRM with a 3 He concentration of 3 He/ 4 He = 4743 μmol/mol was developed. Because 3 He/ 4 He ratio of atmospheric helium is much lower than this, we decided to produce a new 3 He CRM of helium isotopic ratio and the previously prepared 3 He CRM was diluted by the gravimetric method. The concentration of 3 He in the high purity helium gas used for dilution was measured by comparing it with the newly prepared low 3 He concentration CRMs. Abstract :